Determining c-Myb Protein Levels Can Isolate Functional Hematopoietic Stem Cell Subtypes. (22nd January 2015) - Sakamoto, Hiroshi; Takeda, Naoki; Arai, Fumio; Hosokawa, Kentaro; Garcia, Paloma; Suda, Toshio; Frampton, Jon; Ogawa, Minetaro
Abstract: The transcription factor c-Myb was originally identified as a transforming oncoprotein encoded by two avian leukemia viruses. Subsequently, through the generation of mouse models that affect its expression, c-Myb has been shown to be a key regulator of hematopoiesis, including having critical roles in hematopoietic stem cells (HSCs). The precise function of c-Myb in HSCs although remains unclear. We have generated a novel c-myb allele in mice that allows direct observation of c-Myb protein levels in single cells. Using this reporter line we demonstrate that subtypes of HSCs can be isolated based upon their respective c-Myb protein expression levels. HSCs expressing low levels of c-Myb protein (c-Myb low HSC) appear to represent the most immature, dormant HSCs and they are a predominant component of HSCs that retain bromodeoxyuridine labeling. Hematopoietic stress, induced by 5-fluorouracil ablation, revealed that in this circumstance c-Myb-expressing cells become critical for multilineage repopulation. The discrimination of HSC subpopulations based on c-Myb protein levels is not reflected in the levels of c-myb mRNA, there being no more than a 1.3-fold difference comparing c-Myb low and c-Myb high HSCs. This illustrates how essential it is to include protein studies when aiming to understand the regulatory networks that control stem cell behavior. Stem Cells   2015;33:479–490